A hydrophobic, carboxy-proximal region of a light-harvesting chlorophyll a/b protein is necessary for stable integration into thylakoid membranes. - Kohorn, B D (1989)
Proteins synthesized as soluble precursors in the cytoplasm of eukaryotic cells often cross organellar membrane barriers and then insert into lipid bilayers. One such polypeptide, the light-harvesting chlorophyll a/b-binding protein (LHCP), must also associate with pigment molecules and be assembled into the photosystem II light-harvesting complex in the chloroplast thylakoid membrane. A study of the import of mutant LHCPs into isolated chloroplasts has shown that a putative alpha-helical membrane-spanning domain near the carboxy terminus (helix 3) is essential for the stable insertion of LHCP in the thylakoid. Protease digestion experiments are consistent with the carboxy terminus of the protein being in the lumen. This report also shows that helix 3, when fused to a soluble protein, can target it to the thylakoids of isolated, intact chloroplasts. Although helix 3 is required for the insertion of LHCP and mutant derivatives into the thylakoid, the full insertion of helix 3 itself requires additionally the presence of other regions of LHCP. Thus, LHCP targeting and integration into thylakoid membranes requires a complex interaction involving a number of different domains of the LHCP polypeptide.